INTEGRASI EMPAT PILAR PENDIDIKAN (UNESCO) MELALUI PENDIDIKAN HOLISTIK BERBASIS KARAKTER DI SMP MUHAMMADIYAH 1 PRAMBANAN - juliani, wikanti iffah; Widodo, Hendro (Jurnal Pendidikan Islam, 2019)
Abstract Education is an attempt to find information that is useful for life. Learning to know something (learning to know) becomes an effort that is done in getting useful knowledge and that is not useful. Knowledge and experience gained are then applied to solve problems that arise and get a change. This mastery of knowledge will lead students to find their true identity and develop their potential. After all these learning processes are passed, a student will be able to adapt to the environment and carry out his role in the community.  Learning outcomes that students will get depend on the contribution of the curriculum that has been made. Therefore, in making a curriculum, it is pursued according to needs, not fragmented and can reflect all aspects thoroughly and contextually. The integrity requires a good character to make it clearer in bringing out a complete person.